Overcoming the thermodynamic equilibrium of an isomerization reaction through oxidoreductive reactions for biotransformation - Liu, Jing-Jing; Zhang, Guo-Chang; Kwak, Suryang; Oh, Eun Joong; Yun, Eun Ju; Chomvong, Kulika; Cate, Jamie H. D.; Jin, Yong-Su (Nature communications, 2019)
Isomerases perform biotransformations without cofactors but often cause an undesirable mixture of substrate and product due to unfavorable thermodynamic equilibria. We demonstrate the feasibility of using an engineered yeast strain harboring oxidoreductase reactions to overcome the thermodynamic limit of an isomerization reaction. Specifically, a yeast strain capable of consuming lactose intracellularly is engineered to produce tagatose from lactose through three layers of manipulations. First, GAL1 coding for galactose kinase is deleted to eliminate galactose utilization. Second, heterologous xylose reductase (XR) and galactitol dehydrogenase (GDH) are introduced into the ∆gal1 strain. Third, the expression levels of XR and GDH are adjusted to maximize tagatose production. The resulting engineered yeast produces 37.69 g/L of tagatose from lactose with a tagatose and galactose ratio of 9:1 in the reaction broth. These results suggest that in vivo oxidoreaductase reactions can be employed to replace isomerases in vitro for biotransformation. A desired product cannot be obtained at higher concentration than its equilibrium concentration when isomerases are used for biotransformation. Here, the authors engineer in vivo oxidoreductive reactions in yeast to overcome the equilibrium limitation of in vitro isomerases-based tagatose production.